Functional properties and chemical profile of aged carioca beans and cooked under thesteam of autoclave - Juliana Aparecida Correia Bento; Paulo Riceli Vasconcelos Ribeiro; Priscila Zaczuk Bassinello; Menandes Alves de Souza Neto; Rosângela Nunes Carvalho; Edy Sousa de Brito; Márcio Caliari; Manoel Soares Soares Júnior (Ciência Rural, 2023)
ABSTRACT: This study evaluated the changes caused by cooking presoaked aged carioca beans in the autoclave steam, focusing on its bioactive components, antioxidant activity, and nutritional compounds. Additionally, to identify which carioca bean cultivar could preserve the most quantity of bioactive compounds in cooked flour. The cooked flours from Imperador had the highest antioxidant activity (DDPH: 10.58 µmolTrolox·g-1, ABTS: 18.71 µmolTrolox·g-1), anthocyanins (8.08 µg·g-1), and total phenolic content (TPC) (36.69 mg·g-1). The cultivar Gol also retained part of these compounds after cooking. The phenolic and saponin profiles of cooked flours revealed a reduction in phenolic compounds such as catechin, epicatechin, and kaempferol and an increase in soyasaponin-Ba and Bb. The samples Notavel, Dama, and Madreperola, presented the highest amount of soyasaponin-A0. Thus, the cooked flours from Imperador and Gol stood out due to their retention of part of their bioactive compounds, such as polyphenols and group B saponins.